Online Workshop of Article Writing For Scopus Indexed Journals - Agus Purwanto; Khaerul Fahmi; Yoyok Cahyono (CV. AGUSPATI RESEARCH INSTITUTA, 2023)
Publication is an embodiment of intellectual and knowledge dissemination in written works that can be useful for society. A lecturer has a role in contrib-uting to the dissemination of ideas through the publication of scientific papers. The quality of the lecturer's research articles can be seen from the publication in internationally and nationally reputable journals. This community service activity aims to provide training on scientific article writing and publication in reputable international journals for Pamulang University Lecturers. The problems faced by several lecturers experienced obstacles in publishing reputable international journals, namely the lack of insight into the ability to write articles, limited time, busyness, limited language and limited access to journals, availability of online journal subscriptions. The training method is in the form of virtual delivery of material through the zoom application and par-ticipants can discuss, ask questions directly without the need to gather. At the end of the activity, a question and answer session was carried out as a form of evaluation. The results after attending the training, the participants managed to compile and publish several articles in reputable national and international journals.